Formulation and Evaluation of Herbal-Based Hair Dye for Cosmetic Applications - Pingili Divya; Meghana Madugu; M Priyadarshini; Archana Awasthi; Aravind Kencha; Abhiram Reddy; Khaja Mohammed (Asian Journal of Pharmaceutical Research and Development, 2026)
Herbal substitutes that are safe, environmentally friendly, and good for hair health are becoming more popular as people become more conscious of the negative consequences of synthetic hair dyes. Using natural ingredients like amla (Emblica officinalis), methi (Trigonellafoenum-graecum), henna (Lawsoniainermis), indigo (Indigoferatinctoria), hibiscus (Hibiscus rosa-sinensis), bringaraj (Ecliptaalba), shikakai (Acacia concinna), curry leaves (Murrayakoenigii), kalonji (Nigella sativa), and beetroot (Beta vulgaris), a polyherbal hair dye is the subject of this study. The chosen plant ingredients were dried and ground into a powder using the proper ratios to create the herbal dye. Numerous physicochemical parameters, such as stability, moisture content, pH, organoleptic characteristics, and particle size, were assessed for the produced formulation. The color intensity, dyeing effectiveness, and conditioning effects on hair were also evaluated for marketed henna and natural leaves of henna. The results showed that the marketed henna containing herbal hair dye with beetroot powder (F1) had good stability, conditioning qualities, and coloring capabilities without irritating the scalp or damaging the hair. In addition to providing natural coloring, the substances' bioactive components strengthened, nourished, and encouraged hair development. In conclusion, the created polyherbal hair dye has both cosmetic and medicinal advantages and can be a safe and efficient substitute for synthetic dyes. This study demonstrates the potential of herbal formulations with few adverse effects for use in personal care products.